2011
DOI: 10.1371/journal.pone.0020731
|View full text |Cite
|
Sign up to set email alerts
|

Helios Is Associated with CD4 T Cells Differentiating to T Helper 2 and Follicular Helper T Cells In Vivo Independently of Foxp3 Expression

Abstract: BackgroundAlthough in vitro IL-4 directs CD4 T cells to produce T helper 2 (Th2)-cytokines, these cytokines can be induced in vivo in the absence of IL-4-signalling. Thus, mechanism(s), different from the in vitro pathway for Th2-induction, contribute to in vivo Th2-differentiation. The pathway for in vivo IL-4-independent Th2-differentiation has yet to be characterized.FindingsHelios (ikzf2), a member of the Ikaros transcription regulator family, is expressed in thymocytes and some antigen-matured T cells as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 71 publications
(115 reference statements)
3
69
0
Order By: Relevance
“…The ability of aluminum adjuvants to induce a Th2-biased immune response is the basis of the common use of these adjuvants in the induction of allergic diseases in mouse models. More recent studies showed that injection of mice with alum-precipitated protein induced a marked increase of antigen-specific T FH cells in the draining lymph nodes (Serre et al, 2011a,b). Comparison of T FH and non-T FH CD4 T cells suggested that T FH cells rather than Th2 cells were the major subpopulation of IL-4-secreting CD4 T cells (Serre et al, 2011a).…”
Section: The Immune Response To Aluminum-adjuvanted Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of aluminum adjuvants to induce a Th2-biased immune response is the basis of the common use of these adjuvants in the induction of allergic diseases in mouse models. More recent studies showed that injection of mice with alum-precipitated protein induced a marked increase of antigen-specific T FH cells in the draining lymph nodes (Serre et al, 2011a,b). Comparison of T FH and non-T FH CD4 T cells suggested that T FH cells rather than Th2 cells were the major subpopulation of IL-4-secreting CD4 T cells (Serre et al, 2011a).…”
Section: The Immune Response To Aluminum-adjuvanted Vaccinesmentioning
confidence: 99%
“…More recent studies showed that injection of mice with alum-precipitated protein induced a marked increase of antigen-specific T FH cells in the draining lymph nodes (Serre et al, 2011a,b). Comparison of T FH and non-T FH CD4 T cells suggested that T FH cells rather than Th2 cells were the major subpopulation of IL-4-secreting CD4 T cells (Serre et al, 2011a). Taken together these older and more recent studies suggest that aluminum adjuvants induce the differentiation of Th2 cells that drive an eosinophilic inflammatory response and T FH cells that stimulate antibody production.…”
Section: The Immune Response To Aluminum-adjuvanted Vaccinesmentioning
confidence: 99%
“…27 Similarly, Helios provides an additional marker for the discrimination of nTreg cells from iTreg cells, although its specificity remains a concern. 28,29 Nrp-1 also identifies Foxp3 1 cell stability because Nrp-1 1 nTreg cells are more stable compared with Nrp-1 2 nTreg cells. Nrp-1 1 nTreg cells have lower methylation levels in the Treg cell-specific demethylated region.…”
Section: Foxp3 and Treg Cell Subsetsmentioning
confidence: 99%
“…It was suggested that expression of the transcription factor Helios (Ikzf2) might serve as a marker of thymus-derived Tregs (Thornton et al 2010). Unfortunately, it is now realized that Helios is expressed at substantial levels in pTregs induced peripherally by lymphopenia or agonist peptide (Verhagen and Wraith 2010;Darce et al 2012;Gottschalk et al 2012) and is generically induced upon activation of CD4 þ T cells (Akimova et al 2011;Serre et al 2011). Analyses of TCR repertoires in unchallenged mice have shown a high degree of similarity between Tregs in the thymus and peripheral lymphoid organs (Hsieh et al 2006;Pacholczyk et al 2006;Wong et al 2007b), suggesting that tTregs constitute the majority of those pools (there is admittedly a caveat to this argument, which assumes that there is little or no colonization of thymic pools by recirculation from the periphery).…”
Section: Treg Cells Were Identified As Cd4mentioning
confidence: 99%